Peran E-Commerce dalam Meningkatkan Peluang bagi UMKM di Indonesia - Raaken Danendra A W; Silvana Purbawanti; Zella Fathona Aska (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The aim of this research is to find out how the role of e-commerce increases opportunities for MSMEs in Indonesia. The method used in this research is a qualitative approach with literature study as the main data source. We carried out the data collection process by searching literature with the keyword